Thoracic complication detection on chest X-rays using deep learning - Ratul, Rizwanul Hoque; Husain, Farah Anjum; Purnata, Tajmim Hossain; Pomil, Rifat Alam; Khandoker, Shaima (2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.